Financial Governance And Accountability Of Village-Owned Enterprises In Promoting Community Economic Independence - Yunita Fourina Dewi; Susilawati Susilawati; Eljawati Eljawati (STEBIS Bina Mandiri, 2026)
This study aims to analyze in depth the implementation of financial governance and accountability of Village-Owned Enterprises (BUMDes) in Bogor Regency, as well as its impact on social trust and community economic independence. Using a qualitative method with a descriptive-analytical case study design, data were collected through in-depth interviews with 5 key informants (BUMDes Director, Treasurer, BPD, MSMEs, and DPMD), observations, and documentation of financial reports. Data analysis was conducted interactively including data condensation, data presentation, and drawing conclusions based on Stewardship Theory and the concept of hybrid organizations. The results show that BUMDes governance in Bogor Regency has not been running professionally due to strong local political intervention from the Village Government and weak management independence. From an accountability aspect, most BUMDes have not adopted SAK EMKM due to limited technical capacity of human resources. The practice of closed financial reporting and mere bureaucratic formalities creates acute information asymmetry. The impact is a crisis of social trust from the community that triggers apathy and breaks the village economic value chain, so that the target of encouraging economic independence of residents has not been optimally achieved. As a solution, this study reconstructs a participatory accountability model that integrates accounting standards compliance with Sundanese local wisdom (Silih Asih, Silih Asah, Silih Asuh). Radical information transparency and the separation of village political-business boundaries are key to restoring public legitimacy and driving sustainable citizen economic participation.